2020
DOI: 10.1007/s00266-020-01927-4
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling: Percutaneous Collagen Induction (PCI) Therapy for Management of Scars and Photoaged Skin—Scientific Evidence and Review of the Literature

Abstract: Demand for safe, less aggressive and cost-efficient treatment modality to improve skin quality and appearance following scarring or photoaging is increasing steadily. A treatment modality that preserves the epidermis while promoting regeneration rather than cicatrization would be ideal. Percutaneous collagen induction (PCI) therapy or microneedling is claimed to approach this ideal objective. The current comprehensive literature review is intended to analyze the scientific basis supporting this therapeutic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
(87 reference statements)
0
18
0
Order By: Relevance
“…In 1995, a method called subcision was introduced as a minimally invasive way to treat scars using extremely fine needles to disrupt dermal collagen to trigger dermal remodeling and skin resurfacing [ 120 , 121 , 122 ]. This method is now known as microneedling or percutaneous collagen induction (PCI).…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, a method called subcision was introduced as a minimally invasive way to treat scars using extremely fine needles to disrupt dermal collagen to trigger dermal remodeling and skin resurfacing [ 120 , 121 , 122 ]. This method is now known as microneedling or percutaneous collagen induction (PCI).…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…in small cohort clinical studies. A recent review of the evidence available on PCI techniques for scar treatment identified benefits such as little to no side effects and versatility of application [ 120 ]. However, this and other reviews have pointed out the lack of high-quality studies with sufficient numbers of patients following a standardized outcome protocol [ 121 , 122 ].…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…Percutaneous collagen induction therapy, commonly known as microneedling, has proven to be a well-tolerated, minimally invasive office procedure with a minimal downtime, considerable suitability for different skin types with minimal side effects and hence high degree of patient satisfaction. This technique acts through creating micro-channels/wounds inducing a wound healing cascade followed by deposition of newly formed collagen and elastic fibers and clinically evident as more tightened skin [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated the therapeutic efficacy of the combined needling-peeling treatment in different types of wrinkles (Figures 1-4). The maintenance of the integrity of the epidermal layer associated with the deep damage and the restriction of this damage to the area delimited by the microchannel, sparing the surrounding tissues, determines a good therapeutic result, with a low risk of side effects and complications [32,33].…”
Section: Discussionmentioning
confidence: 99%